Optimizing Supply Chain Management to Reduce Food Waste and Loss in Agriculture - Hassan Muntather Muhsin; Hussein Abbas Hameed Abdul; Reddy V. Mallikarjuna (SHS Web of Conferences)
Food waste and loss in agriculture present significant challenges to global food security and resource management. In today's climate, much food is lost from the food system between field and consumer due to inefficiencies in harvesting, storage, transportation, and processing. Beyond economic losses, this problem leads to environmental problems, such as the release of greenhouse gas to the atmosphere from the decomposed waste. The problem statement indicates that although there has been progress in agricultural techniques, the issue of food waste persists. This has been addressed in various ways: improved harvesting techniques, different done storage using, efficient supply chain management, processed and packaged and education and training for farmers. Though the effectiveness of these methods does differ, we need an integrated approach to see some visible results. As a first step of this research, supply chain management is suggested to be optimized as a key strategy to reduce food waste and loss in agriculture. The proposed system intends to slash logistics overhead and coordinate better between farm and market to effectively minimize delays and spoilage of food products supplied to consumers in pristine form. Supply chain management is also integrated with other methods, including better storage solutions and improved processing to obtain a solution encompassing the supply chain. This research results end up in showing that efficient food waste supply chain management can drastically reduce food waste and hence improve food productivity and sustainability. This approach represents a scalable and flexible solution to be implemented in different agricultural contexts that can contribute to global actions for better food security and resource efficiency.